2015
DOI: 10.1002/adma.201502809
|View full text |Cite
|
Sign up to set email alerts
|

Snapping Mechanical Metamaterials under Tension

Abstract: We present a monolithic mechanical metamaterial comprising a periodic arrangement of snapping units with tunable tensile behavior. Under tension, the metamaterial undergoes a large extension caused by sequential snap-through instabilities, and exhibits a pattern switch from an undeformed wavy-shape to a diamond configuration. By means of experiments performed on 3D printed prototypes, numerical simulations and theoretical modeling, we demonstrate how the snapping architecture can be tuned to generate a range o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
207
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(208 citation statements)
references
References 24 publications
0
207
1
Order By: Relevance
“…The beams can then return to their initial configuration when a sufficient reverse force is applied, enabling multiple changes in shape. In [189] the authors created a bistable metamaterial that moves through several metastable states via snap-through buckling when stretched, until it reaches full extension, achieving strains of up to 150%.…”
Section: Multi-stable Structuresmentioning
confidence: 99%
“…The beams can then return to their initial configuration when a sufficient reverse force is applied, enabling multiple changes in shape. In [189] the authors created a bistable metamaterial that moves through several metastable states via snap-through buckling when stretched, until it reaches full extension, achieving strains of up to 150%.…”
Section: Multi-stable Structuresmentioning
confidence: 99%
“…When a mechanical metamaterial is built by arranging such elastic blocks on a square lattice, an instability is triggered under equibiaxial tension resulting in a checkerboard pattern of pores with two different sizes [161,187,188]. Moreover, sequential snap-through instabilities triggered under tensile loading in mechanical metamaterials comprising 1D arrays of curved beams [189] (see Fig. 14(a)) and 2D arrays of rotating units [190] result in large extension and a range of nonlinear mechanical responses.…”
Section: -10 / Vol 69 September 2017mentioning
confidence: 99%
“…Adapted from Ref. [189]. (b) Response of an elastic sheet perforated with a square array of mutually orthogonal cuts under uniaxial tension.…”
Section: Tunable Acoustic Metamaterialsmentioning
confidence: 99%
“…[12][13][14] An emerging opportunity in the engineering of soft machines is to harness these instabilities to achieve new functionalities. [15][16][17] For example, buckling has proven useful in the design of stretchable soft electronics, [18,19] tunable materials, [20][21][22][23] and fluidic actuators. [24] We have previously demonstrated that reversible buckling of elastomeric beams can be used to make a torsional soft actuator.…”
mentioning
confidence: 99%